Predictors of anxiety and depression in patients with oral cancer undergoing radical resection with reconstructive surgery - Kento Kaminogo; Satoshi Yamaguchi; Tatsuya Tokura; Hiroyuki Kimura; Shinichi Kishi; Norihisa Ichimura; Noriyuki Yamamoto; Go Ohara; Hui Chen; Norio Ozaki; Masashi Ikeda; Hideharu Hibi (Oral Oncology Reports)
Objectives: The reduced survival rate and diminished quality of life (QOL) observed in cancer patients with depression have garnered significant attention in recent years. Oral cancer can cause psychological and social stress because its incidence and treatment not only impair oral functions, such as mastication, swallowing, and articulation, but also disfigure the face. In this study, we investigated the factors that predict worsening psychiatric symptoms, such as anxiety and depression, in patients with oral cancer. Materials and methods: Thirty-seven patients with oral cancer who underwent radical resection with reconstructive surgery between 2017 and 2022 were enrolled. The Japanese version of the Hospital Anxiety and Depression Scale (HADS), a screening tool for anxiety and depression, was used to obtain preoperative scores and up to 9-month postoperative scores. Results: The number of patients that exceeded the cut-off values for adjustment disorder and depression was 19 (51.4%) preoperative and 20 (54.1%), 13 (35.1%), and 14 (37.8%) at 3, 6, and 9 postoperative months, respectively. The analysis of covariance showed that the primary site (F = 218.267, p = 0.0216) and marital status (F = 105.758, p = 0.0269) were factors that affected the HADS scores. Conclusion: The risk of postoperative anxiety and depression in patients with oral cancer undergoing radical resection with reconstruction may be increased in patients whose tongue is the primary site and in patients who are single.